2020
DOI: 10.3389/fpsyg.2020.00914
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of Non-paid Task Division in Gay-, Lesbian-, and Heterosexual-Parent Families With Infants Conceived Using Artificial Reproductive Techniques

Abstract: Determinants of Non-paid Task Division T1 performed more childcare tasks at T1. This was still true at T2. The other factors did not significantly contribute to relative time spent on childcare tasks at T2. Conclusion:We had the opportunity to analyze the division of non-paid tasks in families where parenting was necessarily planned and in which gender could not affect that division. Although Feinberg's model of co-parenting suggests that various factors are related to task division, we found that paid work ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 71 publications
(95 reference statements)
0
12
0
1
Order By: Relevance
“…Among gay fathers through surrogacy, biological relatedness seems unrelated to levels of involvement in household and childcare tasks (Tornello et al, 2015 ; van Rijn-van Gelderen et al, 2020 ). However, it may matter for the conflictual dimension of coparenting, as an Italian study (Carone et al, 2017 ) found that non-biological fathers reported less undermining coparenting compared to biological fathers.…”
Section: The (Ir)relevance Of Parent Gender For Coparentingmentioning
confidence: 99%
See 2 more Smart Citations
“…Among gay fathers through surrogacy, biological relatedness seems unrelated to levels of involvement in household and childcare tasks (Tornello et al, 2015 ; van Rijn-van Gelderen et al, 2020 ). However, it may matter for the conflictual dimension of coparenting, as an Italian study (Carone et al, 2017 ) found that non-biological fathers reported less undermining coparenting compared to biological fathers.…”
Section: The (Ir)relevance Of Parent Gender For Coparentingmentioning
confidence: 99%
“…Although heterosexual fathers are increasingly embracing the role of primary caregiver and heterosexual mothers are increasingly taking on the role of primary earner (Schoppe-Sullivan and Fagan, 2020 ), in the majority of heterosexual two-parent families, mothers still remain more engaged in childcare. In gay two-father families, the distinction between primary and secondary caregiver is not always marked; as a result, researchers must sometimes randomly assign the primary caregiving role to one father (van Rijn-van Gelderen et al, 2020 ) or label both fathers primary caregivers (Ellis-Davies et al, 2022 ). Thus, gay two-father families are encouraging a redefinition of caregiving roles, as parental gender is no longer the defining criterion.…”
Section: Fathers As Primary Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…As the present study examined single fathers who were heterosexual or gay, previous research on the family alliance and coparenting across diverse family forms (with respect to parents' sexual orientation) is also relevant. Studies with two-parent families have shown many similarities in parents' management of coparenting-related challenges, regardless of their sexual orientation [34][35][36]. Nonetheless, they have also emphasized some unique and specialized ways in which gay and lesbian parents approach decisions about parenting roles and responsibilities.…”
Section: The Family Alliance and Coparenting In Single-parent Familiesmentioning
confidence: 99%
“…Les couples de même sexe organisent le travail domestique de manière distincte et plus égalitaire en moyenne que les couples de sexes différents [Brewster, 2017 ;Matthews, Tartaro et Hughes, 2002 ;Moore et Stambolis-Ruhstorfer, 2013 ;Patterson, Sutfin et Fulcher, 2004 ;Van Rijn-Van Geldern et al, 2020]. Même si les études françaises sont moins nombreuses, elles tendent à confirmer ces observations dans d'autres pays occidentaux [Descoutures, 2010 ;Vecho, Gross et Poteat, 2011].…”
Section: Couples De Même Sexe : Un Partage Plus éGalitaireunclassified